A new role for dolichol isoform profile in the diagnostics of CDG disorders - Zdrazilova, L; Kuchar, L; Ondruskova, N; Honzik, T; Hansikova, H (Clinica chimica acta; international journal of clinical chemistry, 2020)
Dolichol is a membrane lipid which carries monosaccharides and glycans for N-linked protein glycosylation occurring in the endoplasmic reticulum. Recently, some types of congenital disorders of glycosylation (CDG) have been described as consequences of defects in dolichol biosynthesis and metabolism, yet these types of CDG are not detectable by standard screening methods. The aim of this project was to evaluate the potential of dolichol as a biomarker of CDG. Biological material for this study consisted of urine samples from 75 controls, 6 patients with CDG and 43 patients with suspicion of CDG; samples of the frontal cortex, liver, muscle and heart tissues from 2 patients with mutation in the NUS1 gene and controls. Molecular species profiles of dolichol were analyzed by liquid chromatography combined with tandem mass spectrometry. In the control group, a significant correlation between the ratio of dolichol 18 to dolichol 19 (Dol18/Dol19) and age was found in urine. We established a reference range for Dol18/Dol19 from urine samples. The ratio of Dol18/Dol19 was significantly higher in both urine and tissue samples from patients with mutation in NUS1 in comparison to controls. Our results show a novel diagnostic option for patients with rare congenital disorders of glycosylation.
Keywords: dospělí; Female; Infant; dítě; biologické markery; předškolní dítě; novorozenec; Biomarkers; Adult; mladý dospělý; ženské pohlaví; Adolescent; Congenital Disorders of Glycosylation; lidé; Infant, Newborn; vrozené poruchy glykosylace; Aged, 80 and over; NUS1-CDG; Dolichol; Male; dolichol; kojenec; Aged; Congenital disorders of glycosylation; Child, Preschool; Young Adult; Tandem mass spectrometry; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Dolichols; Middle Aged; mladiství; Humans